Supercritical water oxidation of chlorophenols: Catalytic effect, auxiliary fuels, reaction mechanism, and degradation pathway - Xin Peng; Huiyin Luo; Li Zeng; Zhiwen Cheng; Qingyuan Wang; Bowen Yang (Desalination and Water Treatment)
In this study, the supercritical water oxidation (SCWO) processes of monochlorophenols (ortho-, meta-, and para-chlorophenol, 2-, 3-, and 4-CP), dichlorophenol (2,4-DCP), and trichlorophenol (2,4,6-TCP) were investigated on the basis of experimental data combined with density functional theory (DFT). SCWO experiments were performed in a coiled tubular reactor at 650–800 K, 24 MPa, and 300 % excess oxygen within 5 min with or without catalysts and/or auxiliary fuels. The results indicated that i) the removal efficiency for trichlorophenol was better than those for dichlorophenol and the monochlorophenols; ii) for the three monochlorophenols, the removal efficiencies were in the order of 4-CP > 2-CP > 3-CP; and iii) the chlorophenol removal efficiency increased in the presence of Cu(II) and isopropyl alcohol (IPA). The Fukui index data supported the experimental findings, which showed that i) Cl atoms in the para-position were more susceptible to radical attack than those in the ortho- and meta-positions; ii) the Fukui values of Cl atom(s) were greater than those of carbon, hydrogen, and oxygen atoms; and iii) 2,4-DCP and 2,4,6-TCP could provide more active sites than the monochlorophenols because they possessed more Cl atoms. On the basis of these results, a pathway for the degradation of chlorophenols involving dechlorination, ring opening, and mineralization was proposed.